PERANAN PEMBERDAYAAN PEGAWAI DALAM MENINGKATKAN KINERJA PEGAWAI PADA DINAS PERDAGANGAN PROVINSI SUMATERA SELATAN - Dian Novita Fajar Sari (Jurnal Ilmiah Administrasi Dan Sosial, 2022)
A role is a set of activities or series of actions that are expected to be carried out or carried out by a person or group of people or institutions because of their position in a community. The problem in this study is how the Role of Employee Empowerment in Improving Employee Performance in the South Sumatra Province Trade Office.The purpose of this study was to determine the role of employee empowerment in improving employee performance and inhibiting and supporting factors in improving employee performance. The research method used in this study is to make observations, interviews with informants, and literature study. The statement at the interview included ten questions, with the object of research being employees at the South Sumatra Province Trade Office.     Based on the results of data analysis, the conclusion is that the Role of Employee Empowerment in Improving Employee Performance at the South Sumatra Provincial Trade Office is considered not yet fully good, because of the 9 available indicators, only 4 indicators are carried out well while 5 other indicators still need to be improved again. The five indicators are Quantity, Quality, Time, Cost and Communication between the Head of Service and the Employees. In Employee Empowerment in Improving Employee Performance at the South Sumatra Provincial Trade Office, the five Indicators are very influential. Keywords: Employee Empowerment and Employee Performance